Denotation of Stanza and couplet between the two sonnets (Journal of the College of Education for Women, 2019)
The stanza in the sonnet has been defined as a set of poetic lines followed after proemand be the same meter as that of proem in complete stanza, but in rhyme scheme differentfrom that meter. The couplet is defined as set of poetic lines that followed the stanza and be asthe same meter as that of stanza, but with different rhyme scheme. This definition is approvedby all specialized in field of Andalus literature and it was also proven to them that thisconstruction emptied of indications. This meter has endeavored to prove that that there were adifference in denotation for meaning between the stanza and couplet. Thus, the sonneteershave outweighed the sonnet of the blind "Tutaili" to their sonnets as they felt that his sonnetendowed with characteristics different from theirs. It has been proventhat , via research andanalysis, the sonnet of the blind "Tutaili"has characterized with such denotation. Since then,the sonneteers in Andalus had taken on this sonnet, while sonneteers in Arab Levant countrieshad distinguished the denotation between the stanza and couplet . Their sonnets had beentested in respect to construction and this could have been applied on the sonnet of "Safi Al-Din Al Hali", that being characterized with distinction between the two detonations. Hence,"IbnKhaldun" had nominated it and kept on emphasizing that the sonnet far from affectationsthat others from Arab Levant country have such aspect.